(Meta)Theoretical gateways in studies on assessment and documentation in preschool – a research review with a Scandinavian focus - Ann-Christine Vallberg Roth (Nordisk Barnehageforskning, 2017)
The purpose of this article is to describe and collate search results and analysis of research with a focus on (meta)theoretical gateways in assessment and documentation in Scandinavian preschools between 2006 and 2014, supplemented by delimited international research mainly from 2013-2014. The intention is also to highlight what the research indicates about assessment competence in relation to the (meta)theoretical gateways.  The final search results include 153 national and international studies from sources including the Nordic Base of Early Childhood Education and Care (NB-ECEC, 2006-2012). The results indicate that research into assessment in preschool is still a relatively young and undeveloped field, while the field of documentation, and pedagogical documentation in particular, has a significantly higher standing. As more and more different forms of assessment and documentation assume their place in preschools, it becomes increasingly important to gain knowledge and awareness of the potential benefits, limitations and consequences of various forms and practices for assessment and documentation. Theoretical gateways vary, as do the forms of assessment and documentation used. The analysis indicates that assessment competence can include professional assessment based on a variety of scientific grounds. Regarding the expanded documentation and evaluation task and the preschool’s complex assessment and documentation practices, there is a need for both expanded research and expanded competence, which can focus on a multi-voiced assessment competence.